Apologies in Chinese Restaurants' Responses to Negative Online Reviews and Rapport Management-A Cross-cultural Perspective - Yonghong, Qian (Sinología hispánica. China Studies Review, 2020)
The present study, drawing upon Spencer-Oatey’s (2008) Rapport Management framework, presents an analysis of restaurants’ apologies to customers in Chinese CMC. 100 responses by restaurants to customers’ negative reviews on Dianping.com(a Chinese independent third-party reviewing website similar to TripAdvisor) have been collected for our study, and the method of Rhetorical Move Analysis has been used to identify Apologies and accompanying moves in our data. It is revealed that apologies, along with other accompanying moves such as Thanks, Explanations, Repairs, Openings, Closings, Invitations etc., serve as remedial responses to restore rapport or harmony. Considering the public nature of the open online communication, the linguistic domain of apology (including apology expressions, intensification, repetition, honorifics, endearing addressing terms, pronouns, and selfreferring expressions) and content of apology (Accepting or not accepting responsibility) are properly designed and managed by the restaurants’ response writers in order to repair the relationship with the unsatisfied individual customer on the one hand, while maintaining and protecting the restaurants’ good reputation with the overhearing audience online on the other hand. We also compared our Chinese online apologies with those in English and Japanese as studied by Morrow & Yamanouchi (2020) in order to reveal some cross-cultural similarities and differences. The findings are expected to provide some insights into the area of cross-cultural studies of online apologies, as well as to be valuable to business professionals who increasingly interact with consumers cross-culturally on the internet.